2016
DOI: 10.1515/popets-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

On the Privacy Implications of Location Semantics

Abstract: Mobile users increasingly make use of location-based online services enabled by localization systems. Not only do they share their locations to obtain contextual services in return (e.g., ‘nearest restaurant’), but they also share, with their friends, information about the venues (e.g., the type, such as a restaurant or a cinema) they visit. This introduces an additional dimension to the threat to location privacy: location semantics, combined with location information, can be used to improve location inferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…Second, hardwired user mobility models are used to obtain utility improvements and derive optimal geo-indistinguishability LPPMs [2], or to evaluate a semantic variation of this notion [3]. Non-sporadic location privacy works also hardwired their mobility models on the evaluation data, and typically adopt a Markov model for user mobility to account for temporal correlations [4], [7].…”
Section: Related Workmentioning
confidence: 99%
“…Second, hardwired user mobility models are used to obtain utility improvements and derive optimal geo-indistinguishability LPPMs [2], or to evaluate a semantic variation of this notion [3]. Non-sporadic location privacy works also hardwired their mobility models on the evaluation data, and typically adopt a Markov model for user mobility to account for temporal correlations [4], [7].…”
Section: Related Workmentioning
confidence: 99%
“…Field studies examining the public use of smart glasses revealed that bystanders expressed interest in being asked permission before being recorded, as well as desiring technology to block being recorded [23]. Ağır et al [5] discussed the threat of location data being linked with its semantics as a way of learning about people's behavior (e.g., people go to cinemas after going to restaurants), experimentally showing significant risk for users' semantic location privacy.…”
Section: Related Work 21 Pet Wearables and Privacy Concernsmentioning
confidence: 99%
“…recommendation of restaurants nearby) or to share information about a visited venue, Agir et al [1] present a solution where the semantic dimension of a location can be protected by generalising the semantic tag and locations can be obfuscated.…”
Section: Related Workmentioning
confidence: 99%